Circular entrapment :|tracing the (in)formational contours of F-type high security prisons - Açıkalın, Mesut. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis is a multilayered inquiry on the phenomenon of isolation; isolation understood as a distinct situation and sense of (un)reality that stems from an obsessive dictum of its ontological impossibility as the sole condition of possibility. The F-type High Security Prison, together with the history of penal transformation that led to its formation, is the second central domain of concern. Taking the experience of community as the sole possible (un)ground(ing) of experience, and as an always already resistance to isolation, the thesis first aims to rethink the recent (hi)stories of penal transformation of Turkey in tandem with both antagonistic and cooperative forces that (are) in-formed (through) it. Situating the F-type Prison on the maxim of abstraction that both includes and exceeds disciplinary concerns over the body, it then tries to reimagine the general terrain of the prison as a scenery instituted by a fictional medium which strategically dictates an insistent denial of its own ontological impossibility. Lastly, the thesis attempts to account for the circular entrapment of experience and community that seemingly occurs when faced with this fictional medium enforced as the dictum and condition of existence. Its data composed by participant observations, conversations with prisoners and ex-prisoners, self-reflections, and other ethnographical data, the thesis tries to conceive and explore the field as a community exposed.
Keywords: Prisons -- Turkey.